Dino-soaring - Smallman, Steve (Pearson Education China, 2010)
"Dino-Soaring" is a fun children's book that follows adventurous dinosaurs as they take to the skies. With vibrant illustrations and catchy, rhythmic text, the story captures the excitement of flying and exploration. Young readers are invited to join the dinosaurs on their soaring journey, promoting themes of friendship, adventure, and imagination. It's an engaging read that sparks curiosity about both dinosaurs and the joy of flight!